Homeric hymns, Homeric apocrypha, lives of Homer - Homerus; West, M. L. (Martin Litchfield), 1937-2015 (Cambridge, Mass. Harvard University Press, 2003)
"Performances of Greek epics customarily began with a hymn to a god or goddess - as Hesiod's Theogony and Words and Days do. A collection of thirty-three such poems has come down to us from antiquity under the title "Hymns of Homer." This new Loeb Classical Library volume contains, in addition to the Hymns, fragments of five comic poems that were connected with Homer's name in or just after the Classical period (but are not today believed to be by the author of the Iliad and the Odyssey). Here too is a collection of ancient accounts of the poet's life." "The Hymns range widely in length: two are over 500 lines long; several run only a half dozen lines. Among the longest are the hymn To Demeter, which tells the foundational story of the Eleusinian Mysteries; and To Hermes, distinctive in being amusing. The comic poems gathered as Homeric Apocrypha include Margites, the Battle of Frogs and Mice, and, for the first time in English, a fragment of a perhaps earlier poem of the same type called Battle of the Weasel and the Mice. The edition of Lives of Homer contains The Contest of Homer and Hesiod and nine other biographical accounts, translated into English for the first time."--Jacket.
Homeric hymns. To Dionysus (fragments) ; To Demeter ; To Apollo ; To Hermes ; To Aphrodite ; To Aphrodite ; To Dionysus ; To Ares ; To Artemis ; To Aphrodite ; To Athena ; To Hera ; To Demeter ; To the Mother of the Gods ; To Heracles the Lionheart ; To Asclepius ; To the Dioscuri ; To Hermes ; To Pan ; To Hephaestus ; To Apollo ; To Poseidon ; To Zeus ; To Hestia ; To the Muses and Apollo ; To Dionysus ; To Artemis ; To Athena ; To Hestia ; To Earth Mother of All ; To Helios ; To Selene ; To the Dioscuri ; Hymn fragment -- Homeric apocrypha. Margites ; Cercopes ; Epikichlides ; The battle of the weasel and the mice ; The battle of frogs and mice -- Lives of Homer. The contest of Homer and Hesiod ; (Pseudo- )Herodotus, On Homer's origins, date, and life ; (Pseudo- )Plutarch, On Homer (I) ; (Pseudo- )Plutarch, On Homer (II) ; From Proclus, Chrestomathy I ; From Hesychius of Miletus, Index of famous authors ; Anonymous I, Life of Homer (Vita Romana) ; Anonymus II, The lineage of Homer (Vita Scorialensis I) ; Anonymus III (Vita Scorialensis II) ; Appendix Romana.
Many of these hymns, poems in the apocrypha, and biographical accounts of Homer translated into English for the first time.
Includes bibliographical references and indexes.
Also issued online.
Translated from the Ancient Greek.
Keywords: Homerus -- Early works to 1800.; Homerus -- Authorship -- Early works to 1800.; Homeric hymns -- Translations into English; Greek poetry -- Translations into English; Hymns, Greek (Classical) -- Translations into English; Poets, Greek -- Biography -- Early works to 1800.